Exploring molecular imaging to investigate immune checkpoint inhibitor-related toxicity - Rachel S van der Post; I Jolanda M de Vries; Willemijn A van Dop; Erik Aarntzen; Sandra Heskamp; Hans J P M Koenen; Harm Westdorp; Manfred Kneilling; Eva Peeters; Evelien A J van Genugten; Carla van Herpen (Journal for ImmunoTherapy of Cancer)
Immune checkpoint inhibitors (ICI) boost the endogenous anticancer immunity, evoking long-lasting anticancer responses in a subset of patients with solid tumors. Simultaneously, ICI are also associated with serious toxicities, impacting treatment duration and the quality of life. The proposed processes underlying ICI-related toxicity include T-cell activation and recruitment to non-tumor tissues, involvement of other immune cells and fibroblasts and the host’ microbiome composition. However, the exact mechanisms of these processes remain incompletely understood, hindering clinicians’ ability to predict and identify ICI-related toxicity in the early stages of treatment. Molecular imaging may play a role as a non-invasive biomarker, providing a tool to study ICI-related toxicity. This review discusses the applications of molecular imaging to answer questions regarding the mechanisms, detection, and prediction of ICI-related toxicity. Potential targets and the current state of development of suitable imaging techniques are discussed.